PENGARUH BAURAN PEMASARAN NON KONVENSIONAL TERHADAP KEPUASAN PELANGGAN DENGAN PENDAPATAN KONSUMEN SEBAGAI VARIABEL PEMODERASI ( Studi Kasus Pada Hotel Kusuma Sahid di Surakarta) - Wijiastuti, Sri (JURNAL RISET MANAJEMEN & AKUNTANSI, 2012)
The purpose of this study are (1) Knowing the implementation of non conventional marketing mix of Sahid Kusuma Hotel services consisting of service personnel, physical infrastructure, the service process. (2) Analyze the influence of non-conventional marketing mix of Sahid Kusuma Hotel service consisting of service personnel, physical infrastructure, and service process, to customer satisfaction. (3) Knowing the influence the consumers income as a moderating variable to customer satisfaction. The types of data used in this study are drawn from primary data customers of Sahid Kusuma Hotel. The samples taken are 100 from populations. The results of analysis using hierarchical regression analysis techniques found that the care workers have a significant positive impact on customer satisfaction; Physical infrastructure has a significant positive impact on customer satisfaction; Service process has a significant positive impact on customer satisfaction; Interaction service representatives and service processes with a variable income as moderating effect of consumers not influential to customer satisfaction, and the consumers income as a moderating effect strengthens the influence of physical infrastructure on the level of customer satisfaction of Sahid Kusuma Hotel.